Geographical variation in the prevalence of sensitization to common aeroallergens in adults: the GA2LEN survey. Issue 5 (21st March 2014) - Newson, R. B.; van, R.; Forsberg, B.; Janson, C.; Lötvall, J.; Dahlén, S.‐E.; Toskala, E. M.; Bælum, J.; Brożek, G. M.; Kasper, L.; Kowalski, M. L.; Howarth, P. H.; et al.
Abstract Background Geographical variation in the prevalence of sensitization to aeroallergens may reflect differences in exposure to risk factors such as having older siblings, being raised on a farm or other unidentified exposures. Objective We wanted to measure geographical variation in skin prick test positivity and assess whether it was explained by differences in family size and/or farm exposure. We also compared prevalence in younger and older subjects. Methods Within the Global Allergy and Asthma European Network (GA2LEN) survey, we measured the prevalence of skin prick positivity to a panel of allergens, and geometric mean serum total immunoglobulin E (IgE), in 3451 participants aged 18–75 years in 13 areas of Europe. Estimated prevalence was standardized to account for study design. We compared prevalence estimates in younger and older subjects and further adjusted for age, gender, smoking history, farm exposure, number of older siblings and body mass index (BMI). Results Skin prick test positivity to any one of the measured allergens varied within Europe from 31.4% to 52.9%. Prevalence of sensitization to single allergens also varied. Variation in serum total IgE was less marked. Younger participants had higher skin prick sensitivity prevalence, but not total IgE, than older participants. Geographical variation remained even after adjustment for confounders. Conclusion Geographical variation in the prevalence of skin prick test positivity in Europe is unlikely to be explained by geographical variation in gender, age, smoking history, farm exposure, family size and BMI. Higher prevalence in younger, compared to older, adults may reflect cohort‐associated increases in sensitization or the influence of ageing on immune or tissue responses.